Concerning Diet Duration at Cow’s Milk Protein Allergy. How and When Should Dairy Products Be Introduced Again? - S. G. Makarova; L. S. Namazova-Baranova; G. A. Novik; E. A. Vishneva; M. I. Petrovskaya; S. G. Gribakin (Педиатрическая фармакология)
Cow’s milk proteins (CMP) are the most often cause of allergy in young children. Despite the significant successes in laboratory diagnosis, which also cover allergy in children, food allergy is still a major discussion point in many cases. Successful CMP allergy treatment in children is largely dependant upon the early diagnosis and timely prescription of an eliminatory diet and is defined not only by the actions of specialists (allergologists and dietologists) but also of the primary level doctors. The minimal effective duration of the diet is established by evidence-based studies and is defined in consensus documents on treating children with CMP allergy. Further questions concerning diet duration are resolved according to each unique case. The continuation of a diet should be justified, therefore the necessity of eliminating certain products from a child’s diet is evaluated every 6–12 months. However, at the moment there are no clear ways to predict the duration after which tolerance would appear and thus the duration of a strict eliminatory diet for CMP allergic children. Until recently it was believed that 80–90% of CMP-allergic children form a tolerance over the first 3–5 years of life; however, according to the latest data, the body’s adaptation manifests later. In general, studies show that persisting CMP allergy is characterized by a severe family anamnesis concerning atopic diseases, a longer period between the beginning of CMP intake and the first allergy symptoms, a larger frequency of multiple food reactions and the presence of other allergies. With age a partial CMP tolerance may develop, when dairy products should be introduced in limited amounts. In such cases specialists recommend to introduce milk proteins in tolerable amounts (mainly as part of other products), which, as has been demonstrated, can contribute to the formation of tolerance, while retaining the diagnosis formulation.